2020
DOI: 10.1088/1757-899x/765/1/012050
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Performance of the Pump Station in Pipe Line Transportation System Using PLC Controller and Remote Monitoring

Abstract: In industries, analysis and control of pressure and flow rate control is very difficult, this leads to factory closings and heavy maintenance through PLC and SCADA implementation. Automatic control plays an important role in the continuous operation of the system. In this project, the actual pump performance is tested in terms of pressure, efficiency, and flow rate of the pump for the operating system using a pipeline by crossing pressure in the pipeline with a length of 2 m by connecting pressure sensing equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Due to the short R&D period in China and the strict confidentiality of design and control technology by foreign companies, the emulsion pump station developed in China lags far behind foreign countries in terms of promotion and application. e engineering and construction sector also tends to use imported goods but cannot get permission to use high-end features [12]. According to the public reports, when foreign scholars conduct scientific research, they generally use emulsion pump stations with higher automation level or directly put forward suggestions for improvement or upgrading of the problems exposed in the construction of emulsion pump stations [13].…”
Section: Role Of Emulsion Pump Station In the Project And Development Limitationmentioning
confidence: 99%
“…Due to the short R&D period in China and the strict confidentiality of design and control technology by foreign companies, the emulsion pump station developed in China lags far behind foreign countries in terms of promotion and application. e engineering and construction sector also tends to use imported goods but cannot get permission to use high-end features [12]. According to the public reports, when foreign scholars conduct scientific research, they generally use emulsion pump stations with higher automation level or directly put forward suggestions for improvement or upgrading of the problems exposed in the construction of emulsion pump stations [13].…”
Section: Role Of Emulsion Pump Station In the Project And Development Limitationmentioning
confidence: 99%
“…represented by relay contact, and outputs (to solenoids, motor starters, lamps, power meters and so forth) represented by relay coils. [9,10]. These multi-functions enable the PLCs to perform complex motion and process control applications, and with greater speed as tested by Hussein et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…[9,10]. These multi-functions enable the PLCs to perform complex motion and process control applications, and with greater speed as tested by Hussein et al [10]. It was reported that the ow rate of light oil through the pipeline increases rapidly from 0.65 L/min up to 5.17 L/min.…”
Section: Introductionmentioning
confidence: 99%
“…The control technology mainly includes the traditional signal feedback control form such as pressure and the form of neural network fitting and predictive control. Among them, Hashim [8] used PLC control and remote monitoring to improve the performance of the pump station of the pipeline transmission system. Studzonski [9] introduced the algorithm for controlling the water supply pump by pipeline load and node pressure, which can ensure the required pressure while reducing energy consumption.…”
Section: Introductionmentioning
confidence: 99%